Short, John Rennie (2017). Human Geography. A Short Introduction - Tulla, Antoni F. (Documents d'Anàlisi Geogràfica, 2019)
Short, John Rennie (2017) Human Geography. A Short Introduction Nova York: Oxford University Press, 336 p. ISBN 978-0190679835